Cost Effectiveness Analysis of Antibiotics in Appendicitis Surgery Patients at Kediri City Hospital - Restyana, Anggi; Admaja, Wika; Wibisono, Adi (Program Studi Farmasi Universitas Mandala Waluya, 2024)
Pre and post-appendicitis guideline therapy include broad-spectrum antibiotics before surgery, appendectomy (laparoscopic or open), and follow-up antibiotics post-surgery in complicated cases of appendicitis. The incidence of appendicitis is estimated to be around 100 cases per 100,000 people per year, with a consistent incidence rate in Western countries and an increasing trend in developing regions. In Indonesia, there are 24.9 cases of acute appendicitis per 10,000 people. The use of antibiotics in appendicitis surgery has been widely used. In most studies, it is known that the most widely used types of prophylactic antibiotics are second or third generation cephalosporins or a combination of metronidazole, either given as a single dose, two or three doses. However, there has been no research on direct comparisons between antibiotics. Most studies have not found significant differences in the incidence of SSI. In Indonesia, health financing uses the National Health Insurance system which requires cost-effective therapy. This study aims to determine the cost-effectiveness between the use of cefoperazone-metronidazole and ceftriaxone. The perspective in this study uses the perspective of health care facilities. Costs are observed in two classes of care and effectiveness is measured through the incidence of Surgical Wound Infection. The results of cefoperazone-metronidazole antibiotic therapy compared to ceftriaxone in insurance patients obtained an ICER value of Rp 94,380.68,-. So the use of cefoperazone-metronidazole antibiotics will incur additional costs of Rp 94,380.68,- per increase in therapy outcomes. While in the analysis of the cost-effectiveness of cefoperazone-metronidazole antibiotic therapy compared to ceftriaxone in non-insured patients, the average cost was lower with higher effectiveness with cefoperazone-metronidazole antibiotic therapy than using therapy with ceftriaxone antibiotics. Thus, cefoperazone-metronidazole antibiotics can be considered as the main choice in non-insured patient therapy. In this study, no relationship was found between demographic factors, type of appendicitis and class of care on the incidence of surgical wound infections.